2014
DOI: 10.1103/physreva.90.052520
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic polarizabilities with the Lagrange-mesh method

Abstract: Relativistic dipolar to hexadecapolar polarizabilities of the ground state and some excited states of hydrogenic atoms are calculated by using numerically exact energies and wave functions obtained from the Dirac equation with the Lagrange-mesh method. This approach is an approximate variational method taking the form of equations on a grid because of the use of a Gauss quadrature approximation. The partial polarizabilities conserving the absolute value of the quantum number κ are also numerically exact with s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 41 publications
(97 reference statements)
3
31
0
Order By: Relevance
“…For relativistic multipolar polarizabilities, a simple calculation involving different meshes for the initial and final wave functions and for the calculation of matrix elements was devised in Ref. [23]. This calculation provides very accurate values for all charges Z, for the ground state and excited states of hydrogenic atoms with Coulomb or Yukawa potentials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For relativistic multipolar polarizabilities, a simple calculation involving different meshes for the initial and final wave functions and for the calculation of matrix elements was devised in Ref. [23]. This calculation provides very accurate values for all charges Z, for the ground state and excited states of hydrogenic atoms with Coulomb or Yukawa potentials.…”
Section: Discussionmentioning
confidence: 99%
“…Some remarks on their numerical calculation can be found in Appendix B in Ref. [23]. The integral over ω 1 appearing in Eq.…”
Section: B Two-photon Decay Rates In Lagrange Meshesmentioning
confidence: 99%
See 1 more Smart Citation
“…The prefactors are chosen in (39) such that the unit operator O = 1 is diagonal in the (α, α) representation with (1)…”
Section: Lagrange-mesh Methodsmentioning
confidence: 99%
“…This variational approach has been developed mainly to study non-relativistic problems and found many applications [33][34][35][36][37]. There are only few applications of the Lagrange-mesh method to relativistic systems, mainly for simple cases like hydrogenic atoms [38,39].…”
Section: Introductionmentioning
confidence: 99%